2019
DOI: 10.3390/horticulturae5020036
|View full text |Cite
|
Sign up to set email alerts
|

Relative Salt Tolerance of Four Herbaceous Perennial Ornamentals

Abstract: Salt tolerant ornamental plants can be irrigated with alternative water sources that are typically saline as a sustainable practice for urban landscaping, especially in arid and semi-arid regions. However, the salt tolerance of many ornamentals is not known. An eight-week greenhouse experiment was conducted to assess the relative salt tolerance of four perennial ornamentals, ‘Angelina’ (Sedum rupestre), ‘Autumn Joy’ (S. telephium), ‘Blue Spruce’ (S. reflexum), and ‘Blue Daze’ (Evolvulus glomeratus). The plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
5
18
1
Order By: Relevance
“…In both seasons, raising salinity levels from 1000 to 2500 or 5000 ppm caused steady significant reduction in all of tested growth parameters compared to the control plants. These results are similar to findings of various studies (Farahat, et al, 2013;Breś et al, 2016;Ashour and El-Attar 2017;Ashour and Abdel Wahab, 2017;García-Caparrós and Lao, 2018;Hooks and Niu, 2019;García-Caparrós, et al 2020) who reported reductions in growth traits of ornamental plants due to negative impact of salt stress. Effect of bio-stimulators treatments Data in Table 2, 3, and 4 also revealed that vegetative growth attributes of Vitex trifolia 'Purpurea' plants were dramatically affected by foliar application of the biostimulators treatments.…”
Section: Growth Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…In both seasons, raising salinity levels from 1000 to 2500 or 5000 ppm caused steady significant reduction in all of tested growth parameters compared to the control plants. These results are similar to findings of various studies (Farahat, et al, 2013;Breś et al, 2016;Ashour and El-Attar 2017;Ashour and Abdel Wahab, 2017;García-Caparrós and Lao, 2018;Hooks and Niu, 2019;García-Caparrós, et al 2020) who reported reductions in growth traits of ornamental plants due to negative impact of salt stress. Effect of bio-stimulators treatments Data in Table 2, 3, and 4 also revealed that vegetative growth attributes of Vitex trifolia 'Purpurea' plants were dramatically affected by foliar application of the biostimulators treatments.…”
Section: Growth Parameterssupporting
confidence: 92%
“…In recent study (García-Caparrós et al, 2020) reported decrease in total carbohydrates content in response to salt stress. Further, the reduction in K + and Ca 2+ % is in harmony with that recorded by García-Caparrós and Lao (2018); Hooks and Niu (2019). In the present study the obtained reduction of K + and Ca+ 2 % in leaves as a result of salt stress may be due to physical and chemical similarities between K + and Na + and the tendency of Na + to compete with K + for major binding sites, including control of enzymatic activity which occurs at unfavorable cytosolic K + /Na + ratios.…”
Section: Chemical Constituents Chlorophylls Content and Total Carbohysupporting
confidence: 89%
See 1 more Smart Citation
“…Studies, have shown that quinoa can tolerate moderate (150 mM NaCl) to high levels (750 mM NaCl) of salinity [15]. Moreover, the ability of germination and seedling establishment under saline conditions of quinoa plants is dependent on the cultivar [37,38]. In our experiments we compared the tolerance and the ability of three Denmark quinoa cultivars to adapt to salt and alkali stress taking into account the germination rates and we correlated it with the proline production.…”
Section: Tolerance Of Quinoa Cultivars To the Salt And Alkali Stressmentioning
confidence: 99%
“…For example, Delosperma cooperi (hardy ice plant) was determined to exclude Na + in its shoots effectively and tolerate high Clin plant cells (Niu and Rodriguez, 2006). Sedum telephium (orpine) treated with saline solutions accumulated high K + that may associate with osmotic adjustment (Hooks and Niu, 2019). Another study found that leaf K + concentration of Aloe vera (barbados aloe) and Gazania rigens (syn.…”
mentioning
confidence: 99%